The Legal Sanctions of Corruption Criminal Acts in Indonesia from the Perspective of Abdul Majid An-Najjar's Islamic Legal Philosophy - Al Munawar, Faishal Agil (PT. Riset Press International, 2025)
This article discusses legal sanctions for criminal acts of corruption in Indonesia from the perspective of Abdul Majid An-Najjar's Islamic legal philosophy. Corruption in Indonesia is a serious problem that harms the economy and social justice. This research employs a descriptive-qualitative approach and falls under the category of normative research that examines documents and literature related to legal sanctions for corruption in Indonesia. This study aims to analyze legal sanctions for corruption in Indonesia based on Abdul Majid An-Najjar's Islamic legal philosophy, which emphasizes the principles of justice, equality, and accountability as a foundation for combating corruption. Abdul Majid An-Najjar proposes sanctions that are not only repressive but also educational and effective in providing deterrent effects, using hudud and ta'zir sanctions as a legal basis that aligns with Islamic moral and ethical values. This research also identifies the relevance and challenges of implementing Islamic legal principles in Indonesia's pluralistic legal system, as well as their impact on preventing and eradicating corruption. This study's findings show that applying Islamic legal principles in Indonesia's legal system can contribute to creating a more just and corruption-free legal system.